Cooling Performance Improvement for Two Hot Elastic Plates by Using Double Channels With Rotating Cylinders - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Asme, 2024)
Alternative cooling systems that can be used for thermal management in different technological applications such as in batteries, solar panels, electronic systems, and in diverse heat transfer equipments are needed. This study uses a hybrid channel system with rotating circular cylinders to explore the cooling of two heated elastic plates. The numerical analysis of a coupled fluid-structure-thermal system with rotating cylinders is done using the finite element technique with arbitrary Lagrangian-Eulerian (ALE). The study is carried out for different values of the Reynolds number (Re) in the upper channel flow (between 200 and 1000), the nondimensional rotational speeds of the cylinders (Omega in the range between -1000 and 1000), and the nondimensional location of the cylinders (between 0.4 and 1) taking into account the cooling of both the rigid and elastic plates. Rigid plates have better cooling performance than elastic ones. The cooling performance increases for both rigid and elastic plates, up to 26.1% and 31.7%, respectively, at the maximum upper channel flow Re. For elastic and rigid plates, counter-clockwise (CCW) rotation at maximum speed increases cooling performance by 18.5% and 19%, respectively, but clockwise (CW) rotation increments cooling performance by only 7%. The rigid plate's cooling performance increases by 23.6% when rotation is activated at its maximum speed as opposed to a cooling system without cylinders. Thermal performance varies between 26% and 29% when the cylinder is positioned horizontally differently. By using optimization, the cooling performance increase with rotating cylinders at Re = 200, which is determined to be 73.6% more than that of the case without cylinders. Optimization results in an extra 11.2% increase in cooling performance at Re = 1000 when compared to the parametric computational fluid dynamics (CFD) scenario.
Keywords: cooling channel; rotating cylinders; hot elastic plate; finite element method; optimization